Active metabolites and potential mechanisms of Notopterygium incisum against obstructive sleep apnea Syndrome (OSAS): network analysis and experimental assessment - Liu, Peijun; Tang, Weihua; Zhao, Dong; Zhou, Pan; Hu, Ke (Frontiers in Pharmacology, 2023)
: Notopterygium incisum K.C. Ting ex H.T. Chang, a synonym of Hansenia weberbauer iana (Fedde ex H.Wolff) Pimenov & Kljuykov, is an anti-inflammatory medicinal plant. Although notopterol has been reported to be its primary active metabolite, the other metabolites and their mechanisms of action remain unclear. This study aims to investigate the potential mechanisms by which its active metabolites treat Obstructive Sleep Apnea Syndrome (OSAS) through network analysis and experimental validation. Methods: The metabolites and potential targets of Notopterygium incisum were extracted from public databases. We searched for OSAS-related genes in the Genecards, OMIM, PharmGkb, TTD, and DrugBank databases. Cytoscape 3.9.0 was used to construct the drug-target-disease network and screen for hub genes. Human bronchial epithelial (HBE) cells were cultivated in normoxia and chronic intermittent hypoxia (CIH) medium for 24 h. Interleukin-6 (IL-6), tumor necrosis factoralpha (TNF-α), and prostaglandin E2 (PGE2) were quantified using enzyme-linked immunosorbent assay (ELISA). Prostaglandin-endoperoxide synthase 2(PTGS2) mRNA was detected using RT-qPCR, while PTGS2 and nuclear factor-kappa B (NF-κB) proteins were identified using Western blot analysis.Co-Immunoprecipitation(CoIP) and Western blotting were utilized to evaluate the ubiquitination of PTGS2 in HBE cells. Results: Pterostilbene and notopterol, isolated from Notopterygium incisum, had potential therapeuti c effects on OSAS. The PTGS2 and estrogen receptor alpha (ESR1) hub genes were associated with OSAS. The pathway enrichment analysis focuses on the NF-κB, apoptosis, and HIF-1A pathways. In response to CIH, pterostilbene and notopterol decreased IL-6, TNF-α, and PGE2 levels. The NF-κB pathway was activated by an increase in PTGS2 levels. Pterostilbene promoted proteasome-mediated ubiquitination of PTGS2 protein and reduced PTGS2 levels, inhibiting the NF-κB pathway.This study reveals the active metabolites of Notopterygium incisum and hub genes involved in treating OSAS, which provide a basis for the follow-up development and exploitation of the botanical drug.